THE ANALYSIS OF SYMBOLS IN ANGELS AND DEMONS NOVEL BY DAN BROWN - Ira Abriyani Hafid; Fatimah Hidayahni Amin; Fitriyani Fitriyani (Universitas Negeri Padang, 2015)
This research aimed at finding out symbols which are used in Angels and Demons novel. the meaning of the symbols in Angels and Demons novel, and the effect of the symbols in Angels and Demons novel. This research used descriptive method. The data were analyzed by using semiotic approach that was used to analyze the symbols in Angels and Demons novel. The results of the research show that there are thirteensymbols in the novel, they are Chapel Chigi and Fountain of Four River as settings, Illuminati. The Pyramid and 'Irinacria- Abbacuc and the Angel, Ekstase Sant' Teresa, Eanh, Air, Water. Fire. The Lone Dove. Logo CERN. and West Ponente as objects. The meanings of the symbols are Chapel Chigi is the name of Earth Chapel, Fountain of Four River glorified to the four of rivers. Illuminati is the symbol of ancient brotherhood. Abbacuc and the Angel are prophets who are predicted the destruction of earth, Earth is power. Air is intelligence, Water is emotion, Fire is ardor, The Lone Dove is the symbol of Pagan rvhich represents the angel of peace, Logo CERN is the sign of savagery, and West Ponente is the wind of God. The symbol had affected the whole story, Langdon had solved the marker, found the cardinals, found the assassin, and the Church lllumination, and proved that Illuminati has not died.